2023
DOI: 10.1186/s13293-023-00555-2
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin mediates sex-differences in acclimation to high salt diet in rats

Victoria L. Nasci,
Rawan N. Almutlaq,
David M. Pollock
et al.

Abstract: Introduction Current understanding of sodium (Na+) handling is based on studies done primarily in males. Contrary to the gradual increase in high salt (HS) induced natriuresis over 3–5 days in males, female Sprague Dawley (SD) rats have a robust natriuresis after 1 day of HS. Renal endothelin-1 (ET-1) signaling, through ET receptor A and B, is an important natriuretic pathway and was implicated in our previous dietary salt acclimation studies, however, the contribution of ET receptors to sex-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…However, qualitatively, female mice had a greater intensity of epithelial ET-1 immunoreactivity and this agrees with previously published studies which demonstrated that kidney ET-1 production is enhanced in female rats and women [ 51 ]. It is hypothesized that in female/women greater kidney ET-1 promotes efficient return to sodium balance and buffers blood pressure in response to high dietary salt intake [ 51 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, qualitatively, female mice had a greater intensity of epithelial ET-1 immunoreactivity and this agrees with previously published studies which demonstrated that kidney ET-1 production is enhanced in female rats and women [ 51 ]. It is hypothesized that in female/women greater kidney ET-1 promotes efficient return to sodium balance and buffers blood pressure in response to high dietary salt intake [ 51 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are highly significant as mosquito-borne arboviruses represent a significant threat to humans worldwide; they are also surprising because endothelins are vasoconstrictors, and thus regulate blood flow [11]. However, peptide endothelin signaling may have many other functions, such as the recently discovered regulation of sex differences in salt balance management and the kidney response to high salt intake [12]. In this Special Issue, Makjaroen et al describe how lipopolysaccharide (LPS) tolerance might increase susceptibility to secondary infection and/or viral reactivation, and that, in cases of LPS tolerance, macrophages have reduced glycolysis and mitochondrial activities, decreased anti-viral responses, and a down-regulation of anti-viral genes, such as Mx1 and Isg15.…”
mentioning
confidence: 99%